On the Essential Norm of Multiplications Operators Acting on Cesàro Sequence Spaces (2019)
In this article, we establish an important property about the growth of sequences in the dual space of Cesàro sequence spaces. As a consequence of this fact, we calculate the measure of noncompactness or the essential norm of the multiplication operator Mu acting on Cesàro sequence spaces cesp. © 2019 Julio C. Ramos-Fernández et al.